SOCIAL CAPITAL AND ENTREPRENEURIAL GENETICS IN FORMING BUSINESS SUCCESS - Alfiyana, Siti; Chasanatin, Shinta Miftachul; Susilo, Joko Hadi; Anam, Moh Saiful (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research aims to analyze the influence of social capital and entrepreneurial genetics on entrepreneurial success, both partially and simultaneously. Social capital includes networks, trust, and social norms that support business activities. Entrepreneurial genetics includes innate traits that support ability and success in entrepreneurship. Data was collected through a survey of a number of entrepreneurs in various business sectors. Data analysis was carried out using the multiple regression method to measure the influence of each variable on entrepreneurial success. The research results show that social capital and entrepreneurial genetics have a significant influence on partial entrepreneurial success. Simultaneously, these two variables also make a significant contribution to entrepreneurial success, with social capital showing a more dominant influence than entrepreneurial genetics. These findings show the importance of strengthening social capital and developing entrepreneurial genetic potential in increasing entrepreneurial success.